Produksi Bioetanol Dari Mahkota Nanas Menggunakan Bakteri Zymomonas Mobilis Dengan Variasi Konsentrasi Inokulum Dan Penambahan Nutrisi - Suci Rahmadani; Sri Rezeki Muria; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Depletion of fuel oil encourage to find alternative energy that can be renewable to support requirement energy. Therefore, looked for alternative sources of raw materials and the potential is lignocellulosic biomass. This study uses the crown of the pineapple as the main raw material. This pineapple crown containing cellulose that can be utilized as bioethanol. This study was conducted to produce ethanol by fermentation of cellulose pineapple crown with treatment concentration inoculum at 12%, 14% and 16% with the addition nutrition of urea 0,6 g/l and fermentation time of 24, 48, 72, 96 and 120 hours. The fermentation was conducted in batch process. The result showed that inoculum volume and substrate fermentation also ethanol increased since the population of cells improved. The highest yield of bioethanol is 6% (v/v) at inoculum concentred 14% and the fermentation time 96 hours.keywords : delignification, hydrolysis, fermentation, urea.